Phytoremediation of Mercury and Cyanide Contaminated Soils by Physic Nut (Jatropha curcas L.) and Citronella Grass (Cymbopogon nardus) - A. Silvan Erusani; Nurmaya Arofah; Fabika Azahra; Nurhasni Nurhasni; Titik Inayah (School of Postgraduate Studies, Diponegoro Univer, 2024)
Mercury and cyanide are compounds that have the potential to pollute the environment, both of which are found in the tailing waste of artisanal and small-scale gold mining (ASGM). The purpose of this study was to determine the ability of physic nut (Jatropha curcas L.) and citronella grass (Cymbopogon nardus) to absorb mercury and cyanide in soils polluted with tailings waste based on the value of transfer factors. During this research stage, the remediation of soil polluted with amalgamation tailings and cyanide tailings was carried out for 28 days. Soil sampling was carried out every seven days for 28 days, while root and leaf sampling was carried out on day 28, analysis of mercury and cyanide content in soil and plants using atomic absorption spectroscopy (AAS) and UV-visible spectrophotometer. After 28 days of remediation, mercury and cyanide levels may decrease in soil by 93.7% for mercury and 81.8% for cyanide. The decrease can be caused by absorption and accumulation in plants, where mercury and cyanide accumulate more in physic nut than citronella grass. Physic nut and citronella grass have a transfer factor value of <1 for mercury and cyanide, so they are an excluder plant, except for the accumulation of mercury in physic nut from cyanide tailings soil, which has a transfer factor value of >1, which is an accumulator plant.